1995
DOI: 10.1177/026988119500900402
|View full text |Cite
|
Sign up to set email alerts
|

A new human (psycho)pharmacology tool: the multiple organs coincidences counter (MOCC)

Abstract: We describe a novel instrument which is capable of measuring the uptake of radioligand in human organs in vivo with the administration of very small doses of positron-emitting radioligands. This technique readily detects the displacement or reduced uptake of radioligand when a competitive agonist or antagonist is administered. This system provides no tomographic information, but the small radioactive doses involved mean that investigations can be repeated at regular intervals and that female volunteers can al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…respectively (Malizia et al, 1996). It is interesting to note that comparable data (7 and 39% occupancy at the low and high dose) were obtained using total head counts (Malizia et al, 1996), suggesting that nontomographic methods, which require lower levels of radioactivity compared with tomographic techniques, may be used to determine levels of occupancy in humans (Malizia et al, 1995). In a […”
Section: Occupancy Of Benzodiazepine Binding Sites By Tpa023 21mentioning
confidence: 84%
“…respectively (Malizia et al, 1996). It is interesting to note that comparable data (7 and 39% occupancy at the low and high dose) were obtained using total head counts (Malizia et al, 1996), suggesting that nontomographic methods, which require lower levels of radioactivity compared with tomographic techniques, may be used to determine levels of occupancy in humans (Malizia et al, 1995). In a […”
Section: Occupancy Of Benzodiazepine Binding Sites By Tpa023 21mentioning
confidence: 84%
“…This study found of a (small) antihyperalgesic effect in several parameters including in the size of the hyperalgesic area induced by intracutaneous capsaicin injection and in several muscle painrelated read-outs. Non-selective full agonists such as diazepam, clonazepam, midazolam typically induce strong sedation or sleep already at receptor occupancies between 15% and 30% (Fujita et al, 1999;Malizia et al, 1995;Pauli, Farde, Halldin, & Sedvall, 1991;Shinotoh et al, 1989). Compounds with a better α2/α1-selectivity ratio should permit higher levels of receptor occupancy and hence higher α2-GABA A R activation before reaching dose-limiting sedation.…”
Section: Clinical Studies On Antihyperalgesia By Benzodiazepinesmentioning
confidence: 99%
“…The further application of this methodology 22 should provide unique insights of CNS drug mechanisms in vivo, relating medicinal effects to receptor occupancy. It is anticipated that this line of enquiry will be of considerable interest in psychiatry.…”
Section: Measuring Receptor Occupancy Time Course Of Psychotropic Drmentioning
confidence: 99%
“…This novel approach uses PET radiotracers but sacrifices tomographic information in order to reduce the radiation exposure of the subject to about 100-fold less than a conventional PET study 22 . Instead of using a PET camera, a modified whole body counter, consisting of a small number of large sodium iodide scintillation counters, is configured to detect the coincident gamma radiation emitted by decaying PET radioisotopes.…”
Section: Low Dose Radiotracer Studies Using a Multiple Organs Coincidmentioning
confidence: 99%
See 1 more Smart Citation